Modeling Wheat Susceptibility to Disease - H. Zhao; G. F. Sassenrath; X. Lin; R. Lollato; E. D. De Wolf (Kansas Agricultural Experiment Station Research Reports, 2019)
Fusarium Head Blight (FHB) or head scab is a disease caused by the soil-borneFusariumfungus. The disease occurs frequently in southeast Kansas and can result in reductions in wheat yield and quality because of the mycotoxins developed by the fungus. Timely application of fungicides during the heading period of wheat is one option to reduce the fungus and control the infection rate. This study reports our research on use of fungicides to control head scab and improve wheat yield. We developed a model to predict wheat heading date. Accurate knowledge of wheat stage is the first step in developing a good production management tool for timely application of fungicide for disease control.
Keywords: fusarium head blight; wheat; fungicide